(untitled) (Journal of Public and Nonprofit Affairs, 2024)
Campaigns asking for donations at the checkout of retail stores through rounding-up, donating an amount, or purchasing a token are becoming ubiquitous. The concept of “checkout charity” is really one of impulse giving, i.e., a prosocial activity done under time constraints. Industry reports inform us how much money the corporate campaigns are generating, but we have yet to develop a philanthropic profile of an “impulse giver” or compare them with traditional donors. Using the social heuristics hypothesis, this research helps us to better understand impulse giving and the individuals who engage in it. Women, the middle class, and those who are married or divorced were all more likely to give at the register. In contrast with formal giving, education levels had little relation to giving, and those approaching and over 50 years old were less likely to give. Familiarity with the charity and being Black or African-American correlate with greater amounts donated.